Avaliação do perfil humoral de cães vacinados com Leishmune® e de cães naturalmente infectados procedentes de área endêmica de Leishmaniose Visceral. - Izabela Ferreira Gontijo de Amorim (2007)
Visceral leishmaniasis is a serious illness, being fatal when not treated. The dog represents the main reservoir of the illness in urban and peri urban environment. The Leishmune® is a second generation vaccine that uses subunit Fucose Manose Ligant (FML). Soroepidemiological inquiries aim the detention of soropositive dogs. Considering the similarity between the seroconvertion of vaccinated and these of infected dogs the study of the humoral immune profile of 30 vaccinated and 30 naturally infected dogs was performed through enzyme linked immunossorband assay (ELISA) using the soluble antigen of Leishmania chagasi (ASL) and subunit FML, for the IgGT and subclasses IgG1 and IgG2. Clinical evaluation and parasitological assessment, using PCR of blood spotted in filter paper and ear skin immunohistochemical profile were also done. The results evidenced that of the 30 vaccinated dogs, 83.3% (25) presented none compatible signals the infection and all of them presented statistical significant difference of the values of absorbency when compared with natural infected dogs considering the ELISA-FML for the IgGT and IgG2 subclass and for ELISA-ASL considering the IgG1. The evaluation of the IgG1 and IgG2 profiles for every studied animal showed superior optical density for the former subclass, with the exception of the dogs vaccinated in the ELISA-FML, whose averages were equivalents. The IgG1/IgG2 relation it was inferior to one in all the groups. The vaccinated dogs presented negative results in the PCR evaluation as well as and 19 of them in the ear skin immunohistochemical search. So, different optical density averages of the vaccinated and natural infected dogs, for all the immunoglobulins were observed. However, the results suggest that the type of antigen employed modifies the perception of the immunoglobulin, and that enlargement of the evaluated population must be done for establishment of a possible cut of point.